Strategi Inovasi dalam Industri Kosmetik : Studi Kasus PT Surya Permata dan Tantangan di Pasar Modern - Cintia Nurlaela Aprilia; Dian Putri Aura; Nazwa Aulia Rahayu Kurnia; Mochamad Fadlani Salam (Teewan Journal Solutions, 2025)
This study aims to explore the innovation strategy implemented by PT Surya Permata in the cosmetics industry and the challenges faced in the modern market. Using a descriptive qualitative approach, data were collected through semi-structured interviews with internal company parties directly involved in product development and business strategy. The results show that PT Surya Permata implements a product innovation strategy by adding a variety of scents and dosage forms to suit salon needs, as well as collaborating with beauty clinics through a maklon mechanism. The R&D division plays a role in product formulation and testing before registration with the BPOM. The company also uses synthetic and non-synthetic raw materials whose quality is guaranteed through COA, MSDS, and TDS standards. In marketing, aroma-based differentiation is a key advantage supported by consistent service. Key challenges faced include the dynamics of BPOM regulations and sustainability issues. The company demonstrates awareness of the importance of environmentally friendly and halal products as a form of social responsibility. PT Surya Permata's long-term vision is to maintain product quality and strengthen aroma innovation to meet evolving market needs.